Peculiarities of Linear Induction Machine, Operating at the Mode of Phase Regulator - Karaliūnas, B.; Matkevičius, E.; Radzevičius, L. (Elektronika ir Elektrotechnika, 2009)
The article deals with the characteristics of the linear induction machines (LIM) with two flat inductors operating at the mode of a linear phase regulator (LPR). The mode is executed when shifting one inductor respect to the other within the boundaries of the double pole pitch. There are submitted the results of the experimental and theoretical research concerning LIMs as the linear phase regulator, 85 when one inductor is connected to the source of the voltage and operates at the mode of the stator while the other operates at the mode of the stopping secondary element. There were determined the curves of the variations of the transformation coefficients between the windings of the both inductors, as well as the dependencies of the phase currents, powers and induced electromotive forces on the relative shifting of the inductors. The results received are presented for the first time. The recommendations are worked out for the further investigations on the linear phase regulator to be continued and to be applied with the method of three transformation coefficients and adequate schemes. Ill. 7, bibl. 3 (in English; summaries in English, Russian and Lithuanian).